2022
DOI: 10.1002/jat.4384
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenotoxicity assessment of 3‐(3,4‐dihydroxyphenyl)‐7,8‐dihydroxycoumarin on HepG2/C3A cells and leukocytes

Abstract: 3-(3,4-Dihydroxyphenyl)-7,8-dihydroxycoumarin is a newly synthesized coumarin derivative with a potent antioxidant effect. The aim of the present study is to investigate the safety of this compound, determining the in vitro cytotoxic and genotoxic in human peripheral blood mononuclear cells (PBMC) and in HepG2/C3A cells. Cell viability has been investigated by the trypan blue staining test and MTT assay and the genotoxicity by the comet assay and micronucleus test, using concentrations between 0.01 and 10 μg/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 54 publications
1
2
0
Order By: Relevance
“…Positive and negative results of cytotoxicity of different coumarins have been reported. Our research group recently reported the cytotoxicity studies of 3‐(3,4‐dihydroxyphenyl)‐7,8‐dihydroxycoumarin (Castanha et al, 2023), which is chemically very similar to the coumarin evaluated in the present study. Absence of cellular toxicity, for both PBMC and HepG2/C3A cells, through trypan blue staining and MTT assays, has been reported.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Positive and negative results of cytotoxicity of different coumarins have been reported. Our research group recently reported the cytotoxicity studies of 3‐(3,4‐dihydroxyphenyl)‐7,8‐dihydroxycoumarin (Castanha et al, 2023), which is chemically very similar to the coumarin evaluated in the present study. Absence of cellular toxicity, for both PBMC and HepG2/C3A cells, through trypan blue staining and MTT assays, has been reported.…”
Section: Discussionsupporting
confidence: 60%
“…This absence of genetic toxicity has been previously reported for some other coumarins. Recently, our research group reported absence of genotoxicity of 3‐(3,4‐dihydroxyphenyl)‐7,8‐dihydroxycoumarin also on HepG2/C3A and leukocyte cells (Castanha et al, 2023). 6,7‐Dihydroxycoumarin, also known as esculetin, was administered to Swiss mice, and no genotoxic effects were observed in peripheral blood, liver, bone marrow, and testicular cells, as well as no occurrence of chromosomal mutations in polychromatic bone marrow erythrocytes has been described.…”
Section: Discussionmentioning
confidence: 96%
“…Staining of cells with Trypan Blue to distinguish between dead and alive cells is a standard method of identification. [3,[31][32][33] The interior of inactivated cells is stained with Trypan Blue. Normal living cells have an intact cell membrane that rejects the Tapan Blue staining solution and the cells are not stained.…”
Section: Treatment and Active Staining Of Moldmentioning
confidence: 99%